2020
DOI: 10.1007/s00467-020-04570-y
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab versus cyclophosphamide as first steroid-sparing agent in childhood frequently relapsing and steroid-dependent nephrotic syndrome

Abstract: Background: Approximately 50% of children with steroid sensitive nephrotic syndrome (SSNS) will suffer from frequent relapses or steroid dependency, prompting the use of so-called steroid-sparing drugs. In this pilot study, we compare the efficacy and safety of rituximab to oral cyclophosphamide as first-line steroid-sparing medications. Methods:A prospective open label non-randomized study of children with frequent relapsing or steroid-dependant SSNS. Exclusion criteria were steroid-resistant disease, prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
3
14
1
Order By: Relevance
“…Our study demonstrated a significant and clinically relevant reduction in the mean relapse rate during the 6 months after treatment with rituximab, tacrolimus, and cyclophosphamide compared to 6 months before treatment. The mean prednisolone dosage was significantly lower in all groups, confirming that these drugs are effective in minimizing relapse frequency in children with FRSDNS [1,2,7,8].…”
supporting
confidence: 54%
See 3 more Smart Citations
“…Our study demonstrated a significant and clinically relevant reduction in the mean relapse rate during the 6 months after treatment with rituximab, tacrolimus, and cyclophosphamide compared to 6 months before treatment. The mean prednisolone dosage was significantly lower in all groups, confirming that these drugs are effective in minimizing relapse frequency in children with FRSDNS [1,2,7,8].…”
supporting
confidence: 54%
“…An RCT by Basu et al [8] reported a longer median time to first relapse with rituximab (40 weeks) than with tacrolimus (29 weeks). Another non-RCT showed a higher 1-year relapse-free survival with rituximab (84.2%) than cyclophosphamide (58.6%) [7]. Therefore, rituximab was more effective than cyclophosphamide and tacrolimus in prolonging the remission time.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…About 1-3% of children with nephrotic syndrome have frequent relapses or steroid-dependent nephrotic syndrome. Resistance to steroids or steroid toxicity often prompts administration of other immunosuppressive drugs, such as cyclosporine (CsA), cyclophosphamide, rituximab [3]. and others.…”
Section: Introductionmentioning
confidence: 99%